The Role of the Principal in Realizing a Child-Friendly School at SMP Negeri 1 Semaka, Tanggamus Regency - Wijaya, Rahman; Praja Tuala, Riyuzen; Abdurrahman, Abdurrahman (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of Child-Friendly Schools (CFS) at SMP Negeri 1 Semaka, Tanggamus Regency, with an emphasis on the role of the principal's policies, child-friendly learning, and student participation. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies, with the principal and teachers as key informants. The results show that the principal's policies play a central role in integrating the principles of CFS into school management, particularly in creating a safe, comfortable, and violence-free environment. Child-friendly learning is implemented through conducive classroom management, humanistic communication, and the application of positive discipline without violence. In addition, student participation is facilitated through open and inclusive policies, so that students have space to express opinions and be involved in school decision-making. However, this study also found a gap between the ideal concept of CFS and empirical practice, particularly related to differences in understanding among some school members and parents regarding positive discipline and the unequal courage of student participation. Overall, this study concludes that the success of SRA implementation is largely determined by the strength of the principal's policies, supported by child-friendly learning and a sustainable participatory culture. This research is expected to provide theoretical and practical contributions to the development of Child-Friendly School policies in junior high schools.